Upaya Meningkatkan Pemahaman Siswa Dalam Pembelajaran Matematika Melalui Penerapan Pendekatan Konstruktivisme - Triwahyu Riyatuljannah (Al-Aulad: Journal of Islamic Primary Education, 2018)
This study aims to improve students' understanding on each cycles, and to determine the activities of students and teachers in each cycles activities towards learning mathematics by using constructivism approach. This research uses classroom action research, which is the subject of this research is the students of grade V of Madrasah Ibtidaiyah Negeri (MIN) 1 Bandung City amounting to 43 students consisting of 21 male students and 22 female students. This research instrument consists of students' mathematical description and observation sheet of teacher activity and student activity. Based on data analysis of research results there is increasing understanding of students ranging from pre cycles of 39.5%, the first cycle of 81.3% and the second cycle of 97.6% with very good criteria. In addition, the student activity also increased in each cycle, in the first cycle of 68.7% and the second cycle of 95.8% and teacher activity that increased from cycle I of 83.3% and cycle II reached the maximum score of 100%. The attitude of learners to the learning of mathematics with constructivism approach is very enthusiastic because it has a positive response, score obtained by students exceeds the average score.